Gender-specific weight-control behaviors : Utilizing the Narcotics Information Management System and Community Health Survey in 2020 - Kyung Sun Oh; Euna Han (Journal of Infection and Public Health)
Background: The prevalence of obesity and weight management differ by gender in Korea. This study aims to examine these differences by analyzing the patterns of pharmacological prescriptions of narcotic appetite suppressants and non-pharmacological weight control methods across genders. Methods: This study utilized two datasets: the Community Health Survey (CHS), representing non-pharmacological interventions on a national scale, and the Narcotics Information Management System (NIMS), detailing pharmacological practices for weight control. The CHS provided data on obesity, physical activity, nutrition information, and lifestyle behaviors (smoking, drinking, walking), while NIMS data encompassed the use of narcotic appetite suppressants for weight management. A comparative analysis of the two data sources was conducted. Results: Obesity rates were higher among men in their 30 s (51.3 %) and 40 s (46.5 %), whereas women showed increased obesity in their 50 s (25.7 %) and 60 s (31.4 %). Weight control attempts were more prevalent among women, who were more likely to engage in nutritional interventions and pharmacological treatments, particularly opioid appetite suppressants. Over 60 % of these prescriptions were given to women in their 30 s and 40 s, with phendimetrazine and phentermine being the most commonly prescribed. In men, the use of narcotic appetite suppressants was positively associated with high levels of physical activity (β = 9.16, 95 % CI: 2.92–15.41), while in women, prescriptions were associated with favorable health behaviors (β = 11.63, 95 % CI: 3.54–19.73). Conclusions: It is vital to recommend gender- and age-specific weight control strategies, both non-pharmacological and pharmacological. To prevent misuse, societal consensus on the appropriate prescription of narcotic appetite suppressants is crucial.